Elementy systemu informacyjnego logistyki zaopatrzenia - Chomiak-Orsa, Iwona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Logistics became one of the contemporary management methods. Especially supply system is nowadays logistics' important component. For that reason the proper creation of the Logistics Information System is a very important problem. Every system consists of many components that which affect its performance. It means that every system can perform in effective way only if its components and relation between them will be correct. The same situation is in the case of supply chain information system. So, the aim of the article is to characterize the main elements and relation in logistics information system. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 13-20